2022
DOI: 10.21608/nvvj.2022.141188.1005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinicopathological alterations in mice experimentally infected with Trichenella spiralis and the Nematocidal effect of Tannic acid and Albendazole

Abstract: Trichinella spiralis (T. spiralis) is one of the parasitic nematodes of a highly zoonotic importance. It infects various vertebrates, including human. In this study eighty (n =80) Swiss albino mice were experimentally infected by T. spiralis to assess the nematocidal activity of tannic acid (TA) and albendazole (ABZ) individually or in combination during the intestinal phase of T. spiralis. Mice were divided into 10 equal groups 8 mice for each, (control): noninfected but received saline, (ABZ): non-infected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In the present work, the levels of ALT and AST were significantly elevated in the infected groups compared to the non-infected control group. These findings agreed with Hassan et al (2021a), Basyoni andElsabah (2013), andSwilam et al (2022), who reported elevation in serum ALT and AST in mice infected with T. spiralis due to liver damage by migrating larvae.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present work, the levels of ALT and AST were significantly elevated in the infected groups compared to the non-infected control group. These findings agreed with Hassan et al (2021a), Basyoni andElsabah (2013), andSwilam et al (2022), who reported elevation in serum ALT and AST in mice infected with T. spiralis due to liver damage by migrating larvae.…”
Section: Discussionsupporting
confidence: 91%
“…These findings agreed with Hassan et al (2021a), Basyoni and Elsabah (2013), and Swilam et al . (2022), who reported elevation in serum ALT and AST in mice infected with T. spiralis due to liver damage by migrating larvae.…”
Section: Discussionmentioning
confidence: 99%